Pengelolaan Sistem Kerasipan Elektronik Sebagai Determinan Produktivitas Kerja Pegawai di Kecamatan Solokuro Kabupaten Lamongan - Galuh Faruk Shopi Almahdi; Triesninda Pahlevi (Universitas Negeri Surabaya, 2020)
Abstract The purpose of this study was to determine (1) describe the management of electronic filing system in the Solokuro sub-district, (2) find out how productivite the employees are with the electronic-based filing program in the Solokuro sub-district. This type of research conducted by the author is a type of descriptive research with a quantitative approach. With the subject of research Solokuro District employees. Data collecction techniques with interviews and questionnaries. The results of the study indicate that with an electronic filing system can store documents more safely and reduce damage or authenticity of the archives and employees in finding documents that have been archived easier and faster, and employees are enthusiastic about the electronic filing program to be easier in do the archiving activity.